4x-3=-10-2x-1

Simple and best practice solution for 4x-3=-10-2x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3=-10-2x-1 equation:


Simplifying
4x + -3 = -10 + -2x + -1

Reorder the terms:
-3 + 4x = -10 + -2x + -1

Reorder the terms:
-3 + 4x = -10 + -1 + -2x

Combine like terms: -10 + -1 = -11
-3 + 4x = -11 + -2x

Solving
-3 + 4x = -11 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 4x + 2x = -11 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-3 + 6x = -11 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 6x = -11 + 0
-3 + 6x = -11

Add '3' to each side of the equation.
-3 + 3 + 6x = -11 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = -11 + 3
6x = -11 + 3

Combine like terms: -11 + 3 = -8
6x = -8

Divide each side by '6'.
x = -1.333333333

Simplifying
x = -1.333333333

See similar equations:

| 12x^2-54x-108=0 | | 7x+10=2x-15 | | 33f=315 | | x^2+4x=28 | | 5+.15m=16.25 | | 2-18y-6=-7+3+10y | | 5x-5=3x-3 | | 6x-5=27 | | B-19=29 | | 12x^2-90x-48=0 | | 3x-4-6x+10+9x= | | 15d=90 | | y-3(4-2y)=6(y+1) | | 9x-10=-3+2x+7 | | 4=w-10 | | c+88=155 | | 5x+10+5x+10=90 | | b-21=63 | | 6(6v+6)-5=6v | | 3-7x=-9-4x+3 | | 9x^2-5=1 | | 4x-4=x+11 | | -2m=45+7m | | a+14=26 | | 2x+3y=72 | | 15=9+3x | | 18x^2+5x-3=0 | | -6.6-6x-3.7-4x=-9x+6.2 | | 6x-3(y-1)=4x+8 | | x^2-4=-3 | | 2(k+3)-(7k-7)=-6k | | 3x+1=5x+11 |

Equations solver categories